Corrosion-proof laminated and coated structure and method for manufacturing the corrosion-proof laminated and coated structure
The corrosion-resistant laminate coating structure, featuring a zinclich coating layer and a high solids epoxy resin coating with specific additives, addresses the challenge of maintaining long-term corrosion resistance in marine environments by providing stable and crack-resistant protection.
Patent Information
- Application Number
- JP2024169467
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
Existing corrosion prevention methods for marine structures, such as ports and steel components, face challenges in maintaining long-term corrosion resistance, especially in tidal and splashed areas where coatings can be easily scratched or deteriorate over time.
A corrosion-resistant laminate coating structure is developed, comprising a zinclich coating layer followed by a single layer of high solids epoxy resin coating with specific components like bisphenol A-type or F-type epoxy resin, polyamine compounds, fibrous inorganic compounds, rust-proof pigments, and a thickener, applied in a single coat to achieve a dry film thickness of 0.5 mm or more.
This coating structure provides stable corrosion resistance and cracking resistance even if minor defects or over-thick film portions occur, effectively maintaining long-term protection against corrosion in harsh marine environments.
Smart Images

Figure 2025059113000001 
Figure 2025059113000002 
Figure 2025059113000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a corrosion-resistant laminate coating structure and a method for manufacturing the same. [Background technology]
[0002] Port and offshore structures are designed for use for 50 to 100 years because repair and renewal are difficult. The steel components of port and offshore structures are treated with anti-corrosion treatment so that they can maintain their strength even in severe corrosive environments.
[0003] Methods of corrosion prevention widely used include cathodic protection, paint, lining, and coating with FRP. Among them, cathodic protection is an extremely effective method of corrosion prevention in underwater areas where steel members are completely submerged. However, it is said that cathodic protection cannot fully exert its anticorrosive effect in areas where steel members are not completely submerged, such as tidal areas and splash areas.
[0004] In contrast, anticorrosion treatment using a coating composition effectively prevents corrosion even in tidal or splash areas, but has problems such as the coating being easily scratched or the coating film deteriorating over time. For this reason, there has been a need to develop an anticorrosion treatment method that can maintain anticorrosive properties for a long period of time even in the severe corrosive environment of tidal and splash areas at sea.
[0005] A two-liquid type paint composition consisting of a base agent containing a liquid epoxy resin and a curing agent containing a polyamine is well known as a paint composition used for anticorrosive treatment of ports and marine structures (for example, Patent Document 1). Patent Document 1 describes that the paint composition described contains a solid proton donor, which gradually releases acid in the vicinity of the substrate after the coating film is formed, and suppresses the decrease in adhesion of the coating film caused by the hydroxides of minerals in seawater.
[0006] In addition, the applicant proposed in Patent Document 2 a corrosion-resistant coating structure in which a primer coating is provided at the boundary between the corrosion-resistant metal coating and the zinc-rich coating of an offshore structure, and a thick epoxy resin coating is provided on top of the primer coating. In Patent Document 3, the applicant proposed a method of applying a thick film of epoxy resin paint using a specific coating device as a corrosion-resistant coating method for harbors and offshore structures. In Patent Document 4, the applicant proposed a corrosion-resistant coating method in which a specific water-based undercoat paint is applied to a metal surface with residual rust, and a thick film of an epoxy resin-based topcoat paint is applied on top of the primer paint. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2-255879 [Patent Document 2] JP 2006-218699 A [Patent Document 3] Patent Publication No. 2021-107057 [Patent Document 4] JP 2023-6722 A Summary of the Invention [Problem to be solved by the invention]
[0008] The coating composition described in Patent Document 1 has problems in that it is insufficient in curing property, tends to sag during application, and when applied to a thick film, it takes a long time to dry. The thick coating film of millimeters as described in Patent Documents 2 and 3 is usually formed by applying two coats. This is because, although applying the paint in one coat can achieve process saving, there is concern about the deterioration of corrosion prevention due to insufficient film forming property and coating film defects such as coating film cracking in the formed coating film. In addition, Patent Document 4 describes that an epoxy resin-based topcoat paint may be applied to a thick film in one coat, but in order to form a thick coating film with long-term corrosion prevention properties in one coat, it is necessary to apply the coating film to a sufficient thickness so as not to cause coating film defects.
[0009] When a thick coating layer is formed by one coat of high solid content paint, pinholes may form through the coating layer, and rust may occur on the substrate soon after painting. In addition, when one coat of high solid content paint is used, if the substrate to be painted has narrow areas or bolted joints, etc., where the coating layer is thicker than the surrounding flat areas, stress may concentrate there, which may cause cracks in the coating layer.
[0010] The present invention aims to provide a corrosion-resistant laminated coating structure that, when a thick coating layer is formed by a single coat of paint, has stable corrosion resistance even if minor defects occur in the coating layer depending on the construction conditions, and has excellent crack resistance even if an excessively thick coating portion occurs in the coating layer. [Means for solving the problem]
[0011] The present inventors have studied the above-mentioned problems, and as a result, have found an epoxy resin paint containing a specific epoxy resin, a polyamine compound, a fibrous inorganic compound, a rust-preventive pigment, and a thickener as a paint to be applied in one coat, and have arrived at a corrosion-resistant laminated coating structure in which a coating layer of the epoxy resin paint is provided on a zinc-rich coating.
[0012] That is, the present invention provides: Item 1 A zinc-rich coating layer (I); An epoxy resin coating layer (II) disposed on the zinc-rich coating layer (I), The epoxy resin coating layer (II) is a single layer, The epoxy resin coating layer (II) has a dry thickness of 0.5 mm or more; The corrosion-resistant laminated coating structure, wherein the epoxy resin coating layer (II) is formed from a high-solids epoxy resin paint containing an epoxy resin having an epoxy equivalent of 1000 g / eq or less, a polyamine compound, a fibrous inorganic compound, an anti-rust pigment, and a thickener. Section 2 Item 2. The corrosion-resistant laminate coating structure according to item 1, wherein the epoxy resin is a bisphenol A type epoxy resin and / or a bisphenol F type epoxy resin. Section 3 Item 3. The corrosion-resistant laminate coating structure according to item 1 or 2, wherein the polyamine compound contains an amine compound having an active hydrogen capable of reacting with an epoxy group and a tertiary amine compound. Section 4 4. The corrosion-resistant laminate coating structure according to any one of items 1 to 3, wherein the fiber length of the fibrous inorganic compound is 50 to 1000 μm. Section 5 Item 5. The corrosion-resistant laminate coating structure according to any one of items 1 to 4, wherein the high solid content epoxy resin coating further contains at least one selected from the group consisting of reactive diluents, petroleum resins, talc, silica, silane coupling agents, and antifoaming agents. Section 6 6. The corrosion-resistant laminate coating structure according to any one of items 1 to 5, wherein the high solid content epoxy resin coating material is a two-component type coating material having a component containing the epoxy resin as a main component and a component containing a polyamine compound as a curing agent. Section 7 7. The corrosion-resistant laminated coating structure according to any one of items 1 to 6, which is provided for a port or marine structure. Section 8 Item 8. The method for producing the corrosion-resistant laminate coating structure according to any one of Items 1 to 7, comprising: coating a zinc-rich paint on a substrate surface, drying the zinc-rich coating layer (I) formed by coating the high solid content epoxy resin paint once to form the epoxy resin coating layer (II). Section 9 Item 9. The method for producing a corrosion-resistant laminate coating structure according to item 8, wherein the high solid content epoxy resin coating further contains at least one selected from a reactive diluent, a petroleum resin, talc, silica, a silane coupling agent, and an antifoaming agent. Section 10 Item 8 or 9, wherein the high solid content epoxy resin paint is a paint obtained by mixing a base material containing the epoxy resin with a curing agent containing the polyamine compound, and the high solid content epoxy resin paint contains a fibrous inorganic compound, an anti-rust pigment, a thickener, and further contains at least one selected from a reactive diluent, a petroleum resin, talc, silica, a silane coupling agent, and an antifoaming agent. Section 11 Item 11. The method for producing a corrosion-resistant laminate coating structure according to any one of items 8 to 10, wherein the high solid content epoxy resin coating has a solid content concentration of 80 mass % or more. Regarding. Effect of the Invention
[0013] According to the corrosion-resistant laminated coating structure of the present invention, when a thick coating layer is formed by a single coat of paint, even if minor defects or excessively thick portions occur in the coating layer depending on the application conditions, the coating structure can have stable corrosion resistance and crack resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Base material: The substrate to which the corrosion-resistant laminated coating structure of the present invention is applied includes ferrous metals such as iron, steel, ferroalloy, carbon steel, mild steel, and alloy steel, and non-ferrous metals such as metals and alloys thereof such as aluminum, copper, and zinc. If necessary, the substrate is preferably blasted under conditions equivalent to a rust removal degree Sa2 1 / 2 or more according to ISO 8501-1. The corrosion-resistant laminated coating structure is preferably provided for a harbor or offshore structure, such as a pier, a bridge pier, a dolphin, a revetment, a breakwater, a quay, an artificial island, an immersed tunnel, an offshore airport, an offshore oil facility, an offshore gas facility, an offshore wind power plant, etc.
[0015] Zinc-rich coating layer (I): The zinc-rich coating layer (I), which is the first layer of the corrosion-resistant laminated coating structure of the present invention, is formed by applying a zinc-rich paint to the substrate surface, which is the surface of the substrate. The zinc-rich paint is a paint containing zinc dust at a high concentration, for example, 70% by mass or more in the paint solid content, and is commercially available. In the present invention, the corrosion-resistant laminated coating structure has the zinc-rich coating layer (I), so that stable corrosion resistance can be obtained even if minor defects occur in the epoxy resin coating layer (II) depending on the construction conditions. The reason for this is considered to be that the rust-preventive pigment contained in the epoxy resin coating layer (II) described below dissolves in a corrosive environment, and thus supports the corrosion resistance of defective parts of the epoxy resin coating layer (II) together with the zinc-rich coating layer (I). The zinc-rich paint includes, for example, an organic zinc-rich paint containing an epoxy resin binder and zinc dust, an inorganic zinc-rich paint containing an inorganic binder and zinc dust, and the like. The organic zinc-rich paint includes a water-based organic zinc-rich paint and an organic solvent-based organic zinc-rich paint. In the present invention, it is important that the zinc-rich coating layer (I) contains zinc at a high concentration, and any type of binder and solvent may be used.
[0016] The zinc-rich paint can be applied by a general application method such as brush, air spray, airless spray, roller, etc. Drying after application is usually performed at room temperature, but forced drying may be performed as necessary. Room temperature refers to a temperature at which no temperature manipulation such as forced heating or cooling is performed, although it varies depending on the atmospheric temperature of the environment in which the coating is performed. The drying time is preferably 3 to 72 hours, more preferably 6 to 48 hours.
[0017] Epoxy resin coating layer (II): The epoxy resin coating layer (II), which is the second layer of the corrosion-resistant laminate coating structure of the present invention, is formed by applying a high solids epoxy resin paint onto the zinc-rich coating layer (I) formed on the substrate surface, which is the surface of the substrate.
[0018] The high solid content epoxy resin paint is applied in one coat by a general coating method such as air spray, airless spray, roller, brush, etc. One coat refers to a coating method in which the paint is applied, dried to form a coating layer (single layer), and then the coating layer is not recoated. However, the case in which the paint is recoated on an uncured coated object is included in one coat. In contrast, two coats refer to a coating method in which the paint is applied, a cured coating layer is formed through a drying process of, for example, 3 hours or more, and then the paint is recoated on the cured coating layer. Although two coats tend to provide a coating layer with fewer defects (multiple layers with the same properties), the construction period is long and there is a problem of interlayer peeling after a long period of time. For this reason, by applying the paint in one coat, it is possible to provide long-term corrosion protection to the coated object in a short construction period. Drying after painting is usually performed at room temperature, but forced drying by heating or the like may be performed as necessary. The drying time is preferably 3 to 72 hours, more preferably 6 to 48 hours.
[0019] The zinc-rich coating layer (I) has a dry thickness of 5 μm or more, preferably 10 to 75 μm. The epoxy resin coating layer (II) has a dry thickness of 0.5 mm or more, preferably 0.5 to 6 mm. The above thickness range is the range when the coating layer is applied to the flat portion of the substrate.
[0020] In this specification, the dry film thickness is measured with an electromagnetic film thickness gauge according to JIS K5600-1-7, 5.5.6 (2014) Magnetic Induction Film Thickness Gauge. The measurement point is a flat area where the entire measurement part of the electromagnetic film thickness gauge can be contacted, and the average value of three randomly changed locations within the flat area is taken. Note that the coating area is not flat in narrow areas or recessed areas such as bolt joints, so the coating is thick, and the dry film thickness of each of the zinc-rich coating layer (I) and the epoxy resin coating layer (II) may exceed the above range. The coating film at the area where the angle is less than 180° due to screws or bending is an excessively thick film area that is much thicker than the range of the dry film thickness at the flat area.
[0021] In the corrosion-resistant coating structure of the present invention, the single-layer epoxy resin coating layer (II) disposed as the second layer on the first zinc-rich coating layer (I) is formed of a high-solids epoxy resin paint. The high-solids epoxy resin paint contains an epoxy resin having an epoxy equivalent of 1000 g / eq or less, a polyamine compound, a fibrous inorganic compound, a rust-preventive pigment, and a thickener.
[0022] Epoxy Resin: The epoxy resin is a resin having two or more epoxy groups in one molecule, and has an epoxy equivalent of 1000 g / eq or less. The epoxy equivalent is preferably within the range of 100 to 800 g / eq. By using an epoxy resin having an epoxy equivalent of 1000 g / eq or less, it is effective in improving the crack resistance of an excessively thick film portion that may occur depending on the application conditions.
[0023] Epoxy equivalent refers to the number of grams of resin containing 1 gram equivalent of epoxy groups (g / eq). The value published by the manufacturer should be used. If the manufacturer's published value is unclear, the epoxy equivalent measured in accordance with JIS K 7236 (2009) should be used.
[0024] Specific examples of the epoxy resin include bisphenol-type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol AD type epoxy resin; epoxy ester resins obtained by modifying the above bisphenol-type epoxy resin with dibasic acid or the like; novolac type epoxy resins such as cresol novolac type epoxy resin and phenol novolac type epoxy resin; alicyclic epoxy resin; polyglycol type epoxy resin; hydrogenated bisphenol A type epoxy resin; aliphatic type epoxy resins such as diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, trimethylolpropane polyglycidyl ether, hexahydrophthalic acid diglycidyl ester, glycerin polyglycidyl ether, diglycerin polyglycidyl ether, and polyglycerin polyglycidyl ether; and epoxy group-containing acrylic resins having epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate as a constituent component. These can be used alone or in combination of two or more. The epoxy resin is particularly preferably bisphenol A type epoxy resin and / or bisphenol F type epoxy resin.
[0025] The content of the epoxy resin in the epoxy resin coating layer (II) is preferably 30% by mass or more, and more preferably within the range of 50 to 90% by mass.
[0026] In this specification, the mass (g) of the epoxy resin coating layer (II) refers to the mass (g) of the solid content of the high solid content epoxy resin paint for forming the epoxy resin coating layer (II).
[0027] The solid content refers to the solid residue after removing the volatile components, but the residue may contain liquid components at room temperature. The mass (g) of the solid content refers to the mass (g) of the remaining components when the sample is weighed into a heat-resistant container such as an aluminum foil cup, dried at 110°C for 1 hour, and the volatile components are removed.
[0028] Polyamine compounds: The polyamine compound is a resin having two or more amino groups in one molecule, and includes an amine compound having active hydrogen capable of reacting with an epoxy group.Specific examples of the polyamine compound include aliphatic polyamines, aromatic polyamines, aliphatic polyamidoamines, aromatic polyamidoamines, and amine-based resins of epoxy adduct modification obtained by reacting these polyamines or polyamidoamines with epoxy resins.
[0029] Examples of the aliphatic polyamines include ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, pentaethylenehexamine, and modified polyamines thereof, and examples of the aromatic polyamines include phenylenediamine, xylylenediamine, and modified polyamines thereof, etc. Examples of the polyamidoamines include products such as polyamidoamine obtained by reacting the aliphatic or aromatic polyamines with dimer acid (polymerization product of unsaturated fatty acid) or other polycarboxylic acids, and modified polyamidoamines thereof.
[0030] The polyamine compound also includes tertiary amines that are poorly reactive with epoxy groups. In terms of drying properties and initial corrosion resistance after application in a low-temperature environment, the polyamine compound preferably contains a tertiary amine as a part of its components. Examples of the tertiary amine include dimethylaminomethylphenol, 2,4,6-tris(dimethylaminomethyl)phenol, and tri-2-ethylhexane salt of tris(dimethylaminomethyl)phenol.
[0031] From the viewpoint of stable crack resistance and corrosion resistance, the polyamine compound preferably has an amine value in the range of 50 to 700 mgKOH / g, particularly 150 to 650 mgKOH / g. In this specification, the amine value is the amount (mg) of potassium hydroxide equivalent to the hydrochloric acid required to neutralize the amine contained in 1 g of sample, and the value published by the manufacturer is adopted. When the value published by the manufacturer is unclear, the amine value measured according to JIS K 7237 (1995) is adopted.
[0032] The content of the polyamine compound in the epoxy resin coating layer (II) can be appropriately adjusted, but is preferably 3% by mass or more, more preferably in the range of 5 to 45% by mass. When the polyamine compound contains a tertiary amine compound in addition to an amine compound having active hydrogen, the mass of the tertiary amine compound is preferably 1 to 30% by mass, more preferably 5 to 25% by mass based on the total mass of the polyamine compounds.
[0033] Fibrous inorganic compounds: In the present invention, a fibrous inorganic compound refers to an inorganic compound having a long and thin thread-like shape, and has a fiber length (L) of preferably 50 to 1000 μm, more preferably 100 to 800 μm, a fiber diameter (d) of preferably 1 to 100 μm, more preferably 3 to 80 μm, and an aspect ratio (L / d) of preferably 3 to 200, more preferably 5 to 100. The fiber length (L) and fiber diameter (d) used here are values published by the manufacturer, and when the values published by the manufacturer are unclear, the fiber length (major axis diameter) and fiber diameter (minor axis diameter) of each of 100 primary particles present within a certain area are measured by observation under an electron microscope, and the average values thereof are used. By including inorganic compounds of this type in the high solids epoxy resin paint, a corrosion-resistant laminated coating structure having good crack resistance can be obtained even if excessively thick coating portions occur depending on the application conditions.
[0034] Examples of the fibrous inorganic compound include glass wool, silicon carbide, silicon nitride, wollastonite, sepiolite, chrysotile, amosite, tremolite, zeolite, calcium metasilicate, zonolite, potassium titanate, rock wool, aluminum silicate, carbon fiber, aramid fiber, aluminum borate, needle-shaped calcium carbonate, needle-shaped basic magnesium sulfate, needle-shaped zinc oxide, aragonite-type light calcium carbonate, spindle-shaped light calcium carbonate, satin white, and combinations thereof. Glass wool, rock wool, and wollastonite are particularly preferred. Glass wool is a general term for cotton-like materials made of glass fibers, while rock wool is a general term for materials made from natural rocks or steel slag such as blast furnace slag as the main raw material.
[0035] The content of the fibrous inorganic compound in the epoxy resin coating layer (II) is preferably within the range of 0.1 to 30% by mass, more preferably 1.5 to 20% by mass.
[0036] Anti-rust pigments: The anticorrosive pigment may be any anticorrosive pigment known in the paint field, and there is no limitation on its form, such as a single compound, a composite compound, a composition using a combination of a plurality of these compounds, etc. In the anticorrosive laminate coating structure of the present invention, the thick epoxy resin coating layer (II) formed by one coating contains an anticorrosive pigment, so that stable corrosion prevention can be obtained even if minor defects occur in the epoxy resin coating layer (II) depending on the construction conditions.
[0037] Specific examples of anti-rust pigments include phosphate-based metal compounds such as zinc phosphate, magnesium phosphate, magnesium ammonium phosphate co-eutectoid, magnesium monohydrogen phosphate, magnesium dihydrogen phosphate, magnesium calcium phosphate co-eutectoid, magnesium phosphate co-eutectoid, magnesium nickel phosphate co-eutectoid, calcium phosphate, calcium ammonium phosphate, calcium monohydrogen phosphate, calcium dihydrogen phosphate, calcium fluoride phosphate, aluminum phosphate, and aluminum hydrogen phosphate; phosphate-based metal compounds such as magnesium phosphite, calcium phosphite, magnesium calcium phosphite co-eutectoid, basic zinc phosphite, barium phosphite, manganese phosphite, and calcium hypophosphite; calcium silicate, zinc silicate, aluminum silicate, aluminum orthosilicate, hydrated aluminum silicate, aluminosilicates, borosilicates, beryllosilicates, calcium aluminum silicate, sodium aluminum silicate, and aluminum silicate. Examples of the silicate metal salts include aluminum beryllium, sodium silicate, calcium orthosilicate, calcium metasilicate, calcium sodium silicate, zirconium silicate, magnesium orthosilicate, magnesium metasilicate, manganese silicate, and barium silicate; metal ion-exchanged silica compounds such as magnesium ion-exchanged silica and calcium ion-exchanged silica; condensed phosphate metal compounds such as aluminum dihydrogen triphosphate, aluminum dihydrogen triphosphate-magnesium oxide composite, aluminum tripolyphosphate, and aluminum dihydrogen triphosphate-zinc oxide composite; vanadium metal compounds such as vanadium pentoxide, calcium vanadate, magnesium vanadate, and ammonium metavanadate, a calcined product of manganese oxide and vanadium oxide, and a calcined product of calcium phosphate and vanadium oxide; molybdate metal compounds such as aluminum molybdate, calcium molybdate, and aluminum phosphomolybdate; and the like. These may be used alone or in combination of two or more, or may be a composite of two or more. Furthermore, the anti-rust pigments also include compounds modified or treated with silica, calcium silicate and other silicic acid compounds, magnesium oxide, and the like.
[0038] The anti-rust pigment may be a commercially available product, either alone or in combination. Examples of such commercially available products include "EXPERT NP-1000", "EXPERT NP-1020C", "EXPERT NP-1100", "EXPERT NP-1102" (all of which are product names of Toho Pigment Co., Ltd.), "LF Bosei CP-Z", "LF Bosei MZP-500", "LF Bosei CRFC-1", "LF Bosei M-PSN", "LF Bosei MC-400WR", "LF Bosei PM-300", "LF Bosei PM-308" (all of which are product names of Kikuchi Color Co., Ltd.), "K-WHITE140", "K-WHITE Ca650", "K-WHITE450H", "K-WHITE G-105", "K-WHITE #105", "K-WHITE #82" (all of which are product names of Teika Co., Ltd.), "SHIELDEX C303", "SHIELDEX AC-3," "SHIELDEXC-5" (all manufactured by W.R. Grace & Co.), "Silomask 52," "Silomask 52M," "Silomask 22MR-H" (all manufactured by Fuji Silysia Ltd., product names), and "Novinox ACE-110" (manufactured by SNCZ, France, product name). The content of the rust-preventive pigment in the epoxy resin coating layer (II) is preferably within the range of 0.1 to 30% by mass, and more preferably 1.5 to 20% by mass.
[0039] Thickener: Examples of the thickener include organic bentonite, amide wax, hydrogenated castor oil wax, benzylidene sorbitol, metal soap, oxidized polyethylene, polymerized vegetable oil, polycarboxylic acid amine salt, and combinations thereof. In the corrosion-resistant laminated coating structure of the present invention, the high solid content epoxy resin paint contains a thickener, so that a coating layer with few defects can be formed even with one coat, and stable corrosion resistance can be obtained even if minor defects occur in the epoxy resin coating layer (II) depending on the application conditions.
[0040] The content of the thickener in the epoxy resin coating layer (II) is preferably within the range of 0.1 to 10% by mass, and more preferably 0.2 to 5% by mass.
[0041] High solids epoxy coatings: The high solid content epoxy resin coating material for forming the epoxy resin coating layer (II) preferably further contains at least one selected from a reactive diluent, a petroleum resin, talc, silica, a silane coupling agent, and an antifoaming agent.
[0042] Reactive Diluents: The reactive diluent is preferably an epoxy compound that is liquid at room temperature and becomes a coating film component through a curing reaction, and has a molecular weight lower than that of the epoxy resin. Examples of monoepoxy compounds having one epoxy group include glycidyl ether compounds such as alkyl glycidyl ether, phenyl glycidyl ether, alkylphenyl glycidyl ether, and combinations thereof. The number of carbon atoms in the alkyl group is preferably 1 to 20. Examples of polyepoxy compounds include epoxy group-containing compounds other than the epoxy resin, such as alkyl diglycidyl ether, ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and combinations thereof. The reactive diluent may be either a monoepoxy compound or a polyepoxy compound, or both may be used in combination, but it is preferable to include at least a monoepoxy compound from the viewpoint of workability in thick film coating in one coat.
[0043] The content of the reactive diluent in the epoxy resin coating layer (II) is preferably within the range of 1 to 20% by mass, and more preferably 3 to 15% by mass.
[0044] Petroleum Resin: The petroleum resin is a resin obtained by thermally decomposing naphtha, removing compounds such as ethylene, propylene, butadiene, and polymerizing the remaining fraction in a mixed state. From the viewpoint of crack resistance of the excessively thick film portion, the content of the petroleum resin in the epoxy resin coating layer (II) is preferably within a range of 1 to 30 mass%, more preferably 3 to 25 mass%.
[0045] silica: The high solid content epoxy resin coating material preferably contains silica in order to prevent defects from occurring in the epoxy resin coating layer (II) after one coat. As the silica, silica powder having an average particle size of preferably 1 μm to 20 μm can be used. The average particle size of the silica powder is the median size in the particle size distribution measured by a laser diffraction / scattering method. The content of silica in the epoxy resin coating layer (II) is preferably within the range of 1 to 30% by mass, more preferably 5 to 25% by mass.
[0046] talc: The high solid content epoxy resin coating material preferably contains talc from the viewpoint of crack resistance of the excessively thick film portion of the epoxy resin coating layer (II). The content of talc in the epoxy resin coating layer (II) is preferably within a range of 5 to 35% by mass, more preferably 10 to 30% by mass.
[0047] Silane coupling agent: Examples of the silane coupling agent include compounds having a functional group such as a vinyl group, an epoxy group, an amino group, an imino group, or a mercapto group, and an alkoxysilyl group.Specific examples include trialkoxysilanes having a vinyl group such as vinyltrimethoxysilane and vinyltriethoxysilane, trialkoxysilanes having an amino group such as 3-aminopropyltriethoxysilane and N-(2-aminoethyl)3-aminopropyltrimethoxysilane, and trialkoxysilanes having a glycidyl group such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.The content of the silane coupling agent in the epoxy resin coating layer (II) is preferably within the range of 0.1 to 10% by mass, more preferably 0.5 to 5% by mass.
[0048] Defoamer: The defoaming agent may be a defoaming agent known in the paint field. By containing a defoaming agent in the high solid content epoxy resin paint, a coating layer (II) with few defects can be obtained even when a thick film coating is performed by one coat, and stable corrosion resistance can be obtained even if minor defects occur depending on the application conditions. Examples of the defoaming agent include silicon-based defoaming agents and non-silicon-based defoaming agents. Silicon-based defoaming agents are defoaming agents containing polysiloxane or a modified product thereof, and non-silicon-based defoaming agents are defoaming agents not containing polysiloxane or a modified product thereof. Examples of silicon-based defoaming agents include polysiloxane, fluorine-modified siloxane, amino-modified siloxane, alkyl-modified siloxane, polyether-modified siloxane, higher fatty acid-modified siloxane, carboxyl-modified siloxane, and alcohol-modified siloxane, and examples of non-silicon-based defoaming agents include higher alcohol-based, higher alcohol derivative-based, fatty acid-based, fatty acid derivative-based, paraffin-based, (meth)acrylic polymer-based, and mineral oil-based. The content of the antifoaming agent in the epoxy resin coating layer (II) is preferably within the range of 0.1 to 10% by mass, and more preferably 0.3 to 5% by mass.
[0049] The high solid content epoxy resin paint may contain paint additives such as modifying resin components, coloring pigments, extender pigments, pigment dispersants, surface conditioners, curing catalysts, plasticizers, antifreezing agents, antiskinning agents, preservatives, and organic solvents as necessary. The paint may be in the form of a one-component type or a two-component type consisting of a base agent and a curing agent, but is preferably a two-component type consisting of a base agent containing an epoxy resin and a curing agent containing a polyamine compound. In the case of a two-component type, it is preferable that both the base agent and the hardener contain at least one selected from a thickener, a petroleum resin, talc, and an antifoaming agent. With such a constitution, a coating layer with few defects can be formed even if the base agent and the hardener are mixed at the coating site and applied in one coat, and a corrosion-resistant laminated coating structure having stable corrosion resistance can be obtained even if minor defects occur in the coating layer (II) depending on the construction conditions.
[0050] The high solid content epoxy resin paint is a high solid content paint having a solid content concentration of 80% by mass or more from the viewpoint of film finish. The solid content concentration is preferably 85% by mass or more, more preferably 90% by mass or more. Here, when the paint is a two-part type of paint consisting of a base agent and a curing agent, the solid content concentration of the high solid content epoxy resin paint is obtained by using the paint after mixing the two as a sample and measuring the solid content concentration of the sample. In this specification, the solids concentration (mass %) can be calculated by weighing the mass of the sample remaining after drying when measuring the solids content, and determining the ratio of the mass of the sample remaining after drying to the total mass of the sample before drying. EXAMPLES
[0051] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. In the following examples, "parts" and "%" mean "parts by mass" and "% by mass", respectively. In the examples, a corrosion prevention test was carried out to evaluate the corrosion prevention properties of a corrosion prevention laminated coating structure in which pinholes had occurred, and a crack resistance test was carried out to evaluate the crack resistance of an excessively thick film part in an epoxy resin coating layer. In addition, test coated plates and test specimens necessary for carrying out the corrosion prevention test and the crack resistance test were prepared.
[0052] <Production of high solid content epoxy resin paint> [Manufacturing Examples 1-22] The components listed in the base section of Table 1 were mixed in a container and stirred to obtain a base. Next, the components listed in the hardener section of Table 1 were mixed and stirred to obtain high solid epoxy resin paints No. 1 to No. 22. The fibrous inorganic compounds mixed in the bases of Table 1 are as shown in Table 2.
[0053] [Table 1]
[0054] [Table 2]
[0055] (Note 7) Silica: Silica powder, average particle size 15 μm (Note 8) Epoxy resin 1: Bisphenol F type epoxy resin, epoxy equivalent 190g / eq (Note 9) Epoxy resin 2: Bisphenol A type epoxy resin, epoxy equivalent 190g / eq (Note 10) Epoxy resin 3: Bisphenol F type epoxy resin, epoxy equivalent 1200g / eq (Note 11) Alkyl glycidyl ether: Alkyl glycidyl ether with an alkyl group having 12 to 14 carbon atoms. (Note 12) Magnesium ion-containing silica-based anti-rust pigment: "Silomask 22MR-H" (product name, manufactured by Fuji Silysia Ltd.) (Note 13) Polyamine compound: m-xylylenediamine modified with active hydrogen, amine value 390 (Note 14) Tertiary amine compound: 2,4,6-tris(dimethylaminomethyl)phenol, amine value 620
[0056] <Creating test panels with anticorrosive laminated coating structure> Test coated plates having a corrosion-resistant laminated coating structure for use in the corrosion prevention tests (Examples 1 to 21 and Comparative Examples 1 to 7) were prepared according to the following procedures (1) to (6). The test coated plates had a single epoxy resin coating layer. (1) Prepare a flat steel plate measuring 300 mm in length, 100 mm in width, and 3 mm in thickness as the test substrate. (2) On the surface of this test substrate, which is the substrate surface, a commercially available organic solvent-based zinc-rich paint (polyamide-cured epoxy resin zinc-rich paint, base / hardener mass ratio = 95 / 5, zinc dust content 80%) is applied using an airless spray under conditions of a secondary pressure of 10 MPa and a gun distance of 30 cm so that the dry film thickness of the zinc-rich coating is 25 μm or more and 60 μm or less (details are shown in Table 3). (3) The test substrate coated with organic solvent-based zinc-rich paint is dried at 23°C for one day. (4) On the substrate surface, paint No. 1 to No. 22 of each high solid content epoxy resin paint listed in Table 1 is applied in one coat using an airless sprayer equipped with an air-assisted airless gun so that the dry film thickness of the epoxy resin coating is 0.3 mm or more and 2 mm or less (details are shown in Table 3) under the following conditions: secondary pressure 23 MPa, paint liquid temperature 30°C, assist air pressure 0.5 MPa, and gun distance 30 cm. (5) The test substrate coated with the high solids epoxy resin paint is dried at 23°C for 7 days to obtain a coated test panel. (6) The above steps (1) to (5) were repeated to prepare test coated panels (P-1) to (P-28) by changing the dry film thickness of the zinc-rich coating in (2) above and the type of high solids epoxy resin paint or the dry film thickness of the coating in (4) above, based on the description in Table 3. The test substrate (P-28) was prepared by omitting the above steps (2) and (3), since no zinc-rich paint was applied to the substrate.
[0057] In addition, the coating of the high solid content epoxy resin paint in (4) above was performed under conditions that deviated from the generally recommended coating conditions in this example in order to reproduce minor defects (pinholes).
[0058] <Creating a test specimen with an epoxy resin coating layer in the excessively thick film area> Specimens (Q-1) to (Q-22) with an excessively thick epoxy resin coating were prepared for the crack resistance tests (Examples 22 to 38, Comparative Examples 8 to 12) according to the following procedures (1) to (4). Specimens (Q-1) to (Q-22) were prepared using high solid content epoxy resin paints No. 1 to No. 22. In order to accurately evaluate the crack resistance of only the epoxy resin coating layer, the zinc-rich paint layer underneath was not applied to these specimens. (1) Prepare a steel plate measuring 300 mm in length, 100 mm in width, and 1 mm in thickness to serve as the test substrate. (2) On the substrate surface, which is the surface of this test specimen, each of the high solids epoxy resin paints No. 1 to No. 22 is applied in one coat using an airless paint sprayer under the following conditions: secondary pressure 18 MPa, paint liquid temperature 30°C, gun distance 30 cm, so that the dry film thickness is 5 mm. (3) After painting, quickly fold the substrate into an L shape so that the painted surface is on the inside, and then dry it at 23°C for 7 days. (4) Repeat steps (1) to (3) above, changing the type of high solid content epoxy resin paint in step (2) above, based on the description in Table 4, to prepare test specimens (Q-1) to (Q-22).
[0059] Due to the bending in (3) above, the paint gathers in the bent parts of this test specimen during the drying process, and the bent parts have a much thicker film than the flat parts (vertical and horizontal parts). Note that the painting of the high solid content epoxy resin paint in (2) above is a generally recommended painting condition.
[0060] [Determining the presence of pinholes in epoxy resin coating] The above test substrates (P-1) to (P-28) were visually observed to judge whether or not pinholes were present in the epoxy resin-coated portions. The results are shown in Table 3. Yes: Pinholes penetrating through to the zinc-rich coating layer are visible. None: No pinholes are visible
[0061] [Corrosion resistance test] The above test substrates (P-1) to (P-28) were immersed in a 5% sodium chloride aqueous solution, and after one week and six months, they were removed and the state of the coating was observed. The first week was to examine the initial corrosion resistance after painting, and the six months was to examine the long-term corrosion resistance. The corrosion resistance was evaluated on a four-point scale based on the condition after one week of immersion and the condition after six months of immersion. ◎ and ◯ are pass levels and can be said to have corrosion resistance. The results are also shown in Table 3. ◎: No change at all before and after immersion ○: Slight swelling is observed, but no rust is observed. △: 1 to 5 rust spots observed ×: More than 5 rust spots are observed
[0062] [Table 3]
[0063] [Crack resistance test] Each of the L-shaped specimens (Q-1) to (Q-22) created to reproduce the excessively thick film portion above was subjected to 100 cycles of hot and cold cycle testing (1 cycle: 20±2°C water x 18 hours ⇒ -20°C±3°C x 3 hours ⇒ 50±3°C x 3 hours) as specified in JIS A 6909 (2014), and the appearance of the bent portion as the excessively thick film portion and the horizontal and vertical portions as the flat portion was observed. The crack resistance of each specimen was evaluated on a four-point scale based on the appearance of the bent portion and the horizontal and vertical portions. ◎ and ◯ are pass levels and can be said to have crack resistance. The results are also shown in Table 4. ◎: No cracks were found ◯: No cracks observed, but some roughness △: Some cracks are observed ×: Cracks are clearly observed
[0064] [Table 4]
[0065] The coating conditions of the high solid content epoxy resin paint of the example, which was at a pass level in the crack resistance test, show that the formed epoxy resin coating layer has crack resistance by itself. Therefore, it can be said that the corrosion-resistant laminated coating structure having the same epoxy resin coating layer as the example on the zinc-rich coating layer also has crack resistance.
Claims
1. A zinc-rich coating layer (I); and an epoxy resin coating layer (II) disposed on the zinc-rich coating layer (I), The epoxy resin coating layer (II) is a single layer, The epoxy resin coating layer (II) has a dry thickness of 0.5 mm or more; The corrosion-resistant laminated coating structure, wherein the epoxy resin coating layer (II) is formed from a high-solids epoxy resin paint containing an epoxy resin having an epoxy equivalent of 1000 g / eq or less, a polyamine compound, a fibrous inorganic compound, an anti-rust pigment, and a thickener.
2. 2. The corrosion-resistant laminate coating structure according to claim 1, wherein the epoxy resin is a bisphenol A type epoxy resin and / or a bisphenol F type epoxy resin.
3. 3. The corrosion-resistant laminate coating structure according to claim 1, wherein the polyamine compound comprises an amine compound having an active hydrogen capable of reacting with an epoxy group and a tertiary amine compound.
4. 3. The corrosion-resistant laminate coating structure according to claim 1, wherein the fiber length of the fibrous inorganic compound is 50 to 1000 μm.
5. 3. The corrosion-resistant laminate coating structure according to claim 1, wherein the high solid content epoxy resin coating further comprises at least one selected from the group consisting of reactive diluents, petroleum resins, talc, silica, silane coupling agents and antifoaming agents.
6. The high solid content epoxy resin paint is a two-component type paint containing the epoxy resin as a main component and the polyamine compound as a curing agent. The corrosion-resistant laminated coating structure according to claim 1 or 2.
7. 3. The corrosion-resistant laminated coating structure according to claim 1 or 2, which is provided for a harbor or marine structure.
8. 3. The method for producing the corrosion-resistant laminate coating structure according to claim 1 or 2, comprising the steps of: coating a zinc-rich paint on a substrate surface, drying the zinc-rich coating layer (I) formed, and coating the high solid content epoxy resin paint in one coat to form the epoxy resin coating layer (II).
9. The method for producing a corrosion-resistant laminated coating structure according to claim 8, wherein the high solid content epoxy resin coating further contains at least one selected from the group consisting of a reactive diluent, a petroleum resin, talc, silica, a silane coupling agent, and an antifoaming agent.
10. The high solid content epoxy resin paint is a paint obtained by mixing a base material containing the epoxy resin and a curing agent containing the polyamine compound, The method for producing a corrosion-resistant laminate coating structure according to claim 8, wherein the high solid content epoxy resin paint contains a fibrous inorganic compound, an anti-rust pigment, a thickener, and further contains at least one selected from a reactive diluent, a petroleum resin, talc, silica, a silane coupling agent, and an antifoaming agent.
11. The method for producing a corrosion-resistant laminated coating structure according to claim 8, wherein the high solid content epoxy resin paint has a solid content concentration of 80 mass% or more.
Citation Information
Patent Citations
Coating composition for underwater steel structure
JP1990255879A
Corrosionproof cover structure
JP2006218699A
Corrosion protective coating method for harbor / marine structure
JP2021107057A
Anticorrosive coating method
JP2023006722A